Calculations on the Beam #x2013;Wave Interactions in Coaxial Gyrotron Beam Tunnels - Latsas, G. P.; Moraitou, M. D.; Ioannidis, Z. C.; Tigelis, I. G. (Plasma Science, IEEE Transactions on, 2010)
We present the mathematical formulation and numerical results for the beam-wave interaction in a coaxial waveguide with rectangular slots filled with a lossy dielectric material. The formalism is based on a full-wave analysis and the linearized Vlasov equation. Numerical results are given for all kinds of modes in simplified gyrotron beam tunnels, and the effect of the losses to the parasitic oscillations is examined and discussed.
Keywords: Beam tunnels; beam-wave interactions; beam–wave interaction; coaxial gyrotron beam tunnels; coaxial waveguide; coaxial waveguides; full-wave analysis; gyrotrons; linearized Vlasov equation; lossy dielectric material; mathematical analysis; mathematical formulation; Numerical analysis; parasitic oscillations; rectangular slots; slow-wave structures